Associations of maximum oxygen uptake and body composition with arterial stiffness and blood lipids : a cross-sectional study among physically active females in two different training periods - Haaja, Emma (2024)
In general, physical activity and especially endurance sports are known to reduce the risk of cardiovascular diseases and all-cause mortality. It is also established that increased arterial stiffness and un-optimal levels of blood lipids increase the risk of cardiovascular diseases. Previous studies have shown that endurance training decreases arterial stiffness, particularly in people who have greater arterial stiffness at baseline. In addition, endurance training can lead to increased HDL-cholesterol and decreased LDL-cholesterol and triglyceride levels. The main purpose of this thesis was to determine if the arterial stiffness, blood lipid levels, maximum oxygen uptake or body composition of adult elite Finnish female endurance athletes vary between the training periods of preparation period and competition period. The aim was also to determine if better physical performance and body composition have any associations to arterial stiffness or blood lipid levels. Developmental females and female rugby players were used as controls. Data of this study was based on an on-going three-year follow-up study NoREDS conducted at the University of Jyväskylä.